Effectiveness of Quartet Card Media to Improve Studentsâ Understanding of Musical Diversity in Indonesia in Primary School - *, Karsono (Proceeding of International Conference on Teacher Training and Education, 2016)
In Indonesia, learning of arts subject in elementary school (SD) is not in ideal conditions yet. This is due to the wide scope of material factors, provision abilities elementary art teacher, teaching a limited time, and the limited availability of instructional media. In connection with these problems, this research aims to develop learning media art in elementary school. Strategy development by testing the effectiveness of quartet card media themed musical archipelago which made in the first year of research in 2013. The method used in this research is a true experimental design with two experimental control group design. The research sample were 120 students in fourth level class from six elementary schools in the district of Wonogiri, Sukoharjo, and Karanganyar, Central Java. Data were collected by tests, observations, interviews, and documentation. The results of research shows that quartet card media effectively improves the understanding of students on subjects musical diversity in Indonesia. It could describe, on significant level of p â¤ 0.05 the experimental group of student could increase the average level of significance reached on 0,025.